Advances in GRACE satellite studies on terrestrial water storage: a comprehensive review - Jyoti Karki; Jinming Hu; Yu Zhu; Muhammad Mannan Afzal; Fuming Xie; Shiyin Liu (Geocarto International)
Advancements in the Gravity Recovery and Climate Experiment (GRACE) and its successor, GRACE Follow-on (GRACE-FO), have enhanced our understanding of terrestrial water storage (TWS) dynamics globally. These satellite missions measure gravitational anomalies on Earth’s surface, providing data for monitoring TWS. A review of 234 TWS literature since 2001 shows Asia, particularly China, leads in research output, while North America is notable for research intensity and innovation. Emerging issues in Africa, South America and Oceania highlight the need for further investigation. Key journals reflect growing scholarly interest in TWS dynamics. Methodological variations introduce heterogeneity and challenges in result synthesis. Satellite-based studies have improved TWS monitoring accuracy and spatial resolution. Integrating diverse data sources enhances understanding of TWS dynamics, facilitating water resource management and climate adaptation strategies. Addressing methodological uncertainties and elucidating TWS change drivers are crucial for advancing knowledge and promoting sustainable water management globally.